Perioperative management of pancreaticoduodenectomy for pancreatic ductal adenocarcinoma in a patient with moyamoya disease: a rare case report - Shuhao Bi; Zheng Wang; Hongyu Zhuang; Bo Hu; Lei Liu; Junke Wang; Hongxu Chen; Xiaojiang Ning (Frontiers in Oncology, 2026)
Background Moyamoya disease (MMD) is a rare chronic occlusive cerebrovascular disorder associated with a high risk of perioperative ischemic or hemorrhagic stroke. Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant digestive system tumor with high surgical risk. The coexistence of MMD and PDAC is extremely rare, and no consensus on standardized perioperative management protocols has been established to date. The core clinical challenge lies in balancing the goal of radical tumor resection against the prevention of potentially devastating perioperative cerebrovascular events. Case presentation A 62-year-old Asian man with a 5-year history of asymptomatic MMD (managed with aspirin 100 mg daily) presented with painless obstructive jaundice and 5-kg unintentional weight loss. Imaging examinations demonstrated a 1.5 × 1.4 cm nodular lesion in the pancreatic head, which involved the intramural segment of the common bile duct and the duodenum. The preliminary diagnosis was pancreatic cancer. Cerebral computed tomography perfusion (CTP) showed compensatory cerebral blood volume elevation with a focal ischemic penumbra. The disease was classified as Suzuki stage III. Management and outcomes A multidisciplinary team (MDT) formulated an individualized perioperative strategy: (1) strict hemodynamic regulation with mean arterial pressure (MAP) maintained at 80–100 mmHg, (2) optimized anesthesia with continuous regional cerebral oxygen saturation (rSO2) monitoring, and (3) staged balanced anticoagulation with low-molecular-weight heparin (LMWH) bridging. The patient underwent standard pancreaticoduodenectomy (PD). The patient had an uneventful perioperative course, with no cerebrovascular events or major surgical complications. The final pathological examination confirmed moderately differentiated PDAC (pT1cN0M0, AJCC 8th edition) with R0 resection. During postoperative follow-up, the patient exhibited no tumor recurrence, neurological deficits, or cerebrovascular events. Conclusion For patients with MMD undergoing radical PD, MDT-guided individualized management centered on cerebral perfusion maintenance, hemodynamic stability, and staged anticoagulation may help mitigate perioperative risks and achieve favorable clinical outcomes. This case provides practical experience for clinicians confronted with similarly rare clinical conditions. Given the inherent limitations of a single-case design, its generalizability remains to be validated in larger multicenter cohorts.